Маркшейдерское дело: учебник для вузов - Оглоблин Д. Н. Дмитрий Николаевич; Герасименко Г. И.; Никольский С. И.; Папазов М. Г.; Рудаков М. Л.; Травник С. Ф. (Киев, Гостехиздат, 1960)
Авт. указаны на обороте тит. л.